2015
DOI: 10.1074/jbc.m114.634683
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Biochemical, and Biophysical Characterization of Idelalisib Binding to Phosphoinositide 3-Kinase δ

Abstract: Background: Idelalisib is a PI3Kδ inhibitor used to treat hematological malignancies.Results: Idelalisib is selective, noncovalent, reversible, and ATP-competitive.Conclusion: The crystal structure helps explain the potency and selectivity of idelalisib. The biophysical and biochemical data clarify the details of the inhibitor's interactions with PI3Kδ.Significance: Its use in humans makes it important to understand how idelalisib inhibits PI3Kδ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 34 publications
3
138
0
1
Order By: Relevance
“…In crystal structure evaluation of PI3Kd in complex with idelalisib, the electron density of idelalisib showed that there was no The reversibility of idelalisib binding was also demonstrated using surface plasmon resonance studies, with saturable, dose-response interaction with p110d, a very fast on-rate and a moderate off-rate. The response signal in these studies returned to the baseline level during the dissociation phase, indicating complete dissociation, in contrast with the control agent (wortmannin), which was irreversibly bound to p110d [18].…”
Section: Introductionmentioning
confidence: 51%
“…In crystal structure evaluation of PI3Kd in complex with idelalisib, the electron density of idelalisib showed that there was no The reversibility of idelalisib binding was also demonstrated using surface plasmon resonance studies, with saturable, dose-response interaction with p110d, a very fast on-rate and a moderate off-rate. The response signal in these studies returned to the baseline level during the dissociation phase, indicating complete dissociation, in contrast with the control agent (wortmannin), which was irreversibly bound to p110d [18].…”
Section: Introductionmentioning
confidence: 51%
“…The crystal complex of PI3Kd with idelalisib revealed a type II binding that is similar to that of another selective PI3Kd inhibitor, PIK39 [100]. Idelalisib adopts a propeller-shaped conformation with the DFG motif posing in an 'out' conformation [101]. The 5-fluoroquinazolinone moiety squeezes into an induced hydrophobic specificity pocket.…”
Section: Approved Lipid Kinase Inhibitorsmentioning
confidence: 96%
“…The ethyl group binds in a hydrophobic pocket and the phenyl group extends into a hydrophobic region that is close to the solvent front. The hinge hydrogen bond, which is a highly conserved feature for PI3K inhibition [102], is formed between Val828 and the purine moiety that occupies the adenine pocket [101] ( Figure 14B,C). Besides being approved for CLL, idelalisib has also been granted accelerated approval for relapsed follicular B-cell non-Hodgkin lymphoma and relapsed small lymphocytic lymphoma [103,104].…”
Section: Approved Lipid Kinase Inhibitorsmentioning
confidence: 97%
“…Furthermore, the quinazolinone derivatives as novel PI3Kd selective inhibitors have the same structure skeleton with idelalisib, so the co-crystal structure of PI3Kd protein with idelalisib was downloaded from the Protein Data Bank (PDB ID: 4XE0) for the molecular docking study. 29 …”
Section: Data Setsmentioning
confidence: 99%